The Production of the Francophone: A Discursive Construction (Gragoatá, 2021)
The present research proceeds with a discursive analysis of the major phases in the evolution of discourse on the French-speaking world on the one hand and the French-speaking person on the other: when these two objects are being constituted, a strong convergence between them appears, followed by a spectacular divergence; a divergence that will produce ambiguities and confusions whose effects on representations, positions and actions will be studied. The study concludes that it is necessary to take into account the specific characteristics of each of the cultural areas of the Francophonie.